To study and recommend measures to make fkm administration block be more energy efficient - Aina Syafiza, Jamalulail (2013)
Growing demands for sensible use of energy and demands for the better quality of indoor environment lead to seeking of the good solutions for energy efficiency, energy consumption and conservations in buildings. In this research, an attempt is made to identify areas and propose recommendations on effective ways to decrease energy usage in order to make the existing Administration block of the Faculty of Mechanical Engineering in UMP, Pekan be more energy efficient. In order to identify the parameter to take into consideration for this study, methodologies for this study are divided into four phases. In the first phase, more study and literature survey of related journal and articles were conducted to understand key energy efficiency parameters. In the second phase, a visit and close observation were conducted in the FKM Administration block. Next, the energy efficiency problem and the comfort level parameters in the FKM Administration block was analyzed. Last but not least, as the most important part in this study, recommendations for making the FKM Admin block to be more energy efficient are made based on the previous phrases and their parameters stated above. The energy efficiency initiatives shall be implemented under three different groups of strategies; namely No-Cost measures, Low Cost measures and High Cost Measures. For No-Cost measures, a comprehensive awareness programme could be held among staffs and students to support and strengthens the UMP’s overall energy efficiency object ives. Some recommendations also made for Low-Cost measures such as installation of internal kWh meters and change of the lighting system. Recommendation on High-Cost measures includes delayed air-condition compressor start-up and early shut-off, replacement of current air-conditioning regulators and installation of split-unit airconditioning systems for lecture rooms. If the recommendations are implemented in FKM, it will incur a significant change in the culture of the electricity users in FKM itself and the electricity bill will definitely decrease.